2020
DOI: 10.1111/jocn.15344
|View full text |Cite|
|
Sign up to set email alerts
|

Identifying the experiences of new graduate nurses during the transition period to practice as a professional nurse

Abstract: Transition from theoretical knowledge to real-life practice is often challenging, emotionally exhausting and stressful for nurses in acute settings, to deliver safe nursing care in an environment of increased accountability, responsibility of patient care and heavy workloads.These circumstances are common across various regions, as for instance; Solutions (2016) indicated that increasing rate of turnover has been observed with the approximate value of 18.2% in the hospitals located in north-east, which not onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…The findings are in line with the reports by Salem Alghamdi & Ghazi Baker and Sajadi Hezaveh et al, whose mean age of the participants was 24 and 27.84 years respectively. 14 , 37 The participants were mostly females 240 (85%) in study by Parker et al 38 More than half of the participants 205 (65.3%) were working in the specialty care units/wards, and 231 (73.6%) of the participants had less than 1 year of experience, which was consistent with the reports by Sajadi Hezaveh et al (6.76±4 months), and Casey et al (<1 year). 37 , 39 Though majority participants 278 (88.5%) in the present study had at least one preceptor during their orientation which was a bit higher against the study by Parker et al among 144 (63%) new graduate nurses.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The findings are in line with the reports by Salem Alghamdi & Ghazi Baker and Sajadi Hezaveh et al, whose mean age of the participants was 24 and 27.84 years respectively. 14 , 37 The participants were mostly females 240 (85%) in study by Parker et al 38 More than half of the participants 205 (65.3%) were working in the specialty care units/wards, and 231 (73.6%) of the participants had less than 1 year of experience, which was consistent with the reports by Sajadi Hezaveh et al (6.76±4 months), and Casey et al (<1 year). 37 , 39 Though majority participants 278 (88.5%) in the present study had at least one preceptor during their orientation which was a bit higher against the study by Parker et al among 144 (63%) new graduate nurses.…”
Section: Discussionsupporting
confidence: 74%
“… 38 Most participants 169 (53.8%) had unit orientation duration to less than or equal to four weeks, and the same has been reported in study by Parker et al 38 The roles expected to be performed were the most reported difficulty among the participants 220(70%) in their transition period and similar findings have been reported by Salem Alghamdi and Ghazi Baker. 14 The difficulties felt in the various professional tasks could detrimentally affect the quality of care provided by the new nursing graduates. 40 In the present study, skills that the new nursing graduates were uncomfortable performing independently were ventilator care/management 161 (51.30%), chest tube care 142 (45.20%), central line care 109 (34.7%), code/emergency responses 104 (33.10%), and tracheostomy care 88 (28%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nursing skills develop over time, and upon transition, NGNs can demonstrate rudimentary skills but require support to prioritise patients' needs [6]. During this period, NGNs often experience attrition [7,8] due to insubstantial support [9] and conflicting expectations of nursing practice compared to the actuality of the role [7]. During this stressful period, insufficient self-assurance can hamper NGNs' potential to cope efficiently [10].…”
Section: Introductionmentioning
confidence: 99%